Analisis Faktor Risiko Keluhan Subjektif Gangguan Muskuloskeletal (MSDs) pada Guru dan Murid SMA Akibat Pembelajaran Jarak Jauh di Bogor - Azizie, Heykal Aldaffa; Susilowati, Indri Hapsari Hapsari (UI Scholars Hub, 2022)
The COVID-19 pandemic has forced many community activities to be limited, including the education aspect in Indonesia, which implements online learning (PJJ). This online learning makes all learning activities being online and requires teachers and students to be in front of their gadgets to carry out online learning. This PJJ activity certainly has an ergonomic risk that causing musculoskeletal disorders (MSDs). This study aims to determine the risk of ergonomics during online learning activities for high school teachers and students in Bogor. The method in this study is a cross-sectional study design using the Nordic Musculoskeletal Questionnaire and additional questionnaire that distributed online and this study was conducted on 496 teachers and students from public and private schools. The variables studied were individual factors, work factors, work equipment factors, and subjective complaints of MSDs. The results show that there are more than 60% of teachers and students in both schools experience musculoskeletal disorders subjective complaints. Most complaints are felt in the neck, shoulders, upper back, lower back, hands, and feet. A significant relationship was also found between the PJJ period, PJJ duration, PJJ frequency, repetition movement, static movement, frequency of physical activity, chair condition, and table condition.